2006
DOI: 10.1080/08035250600575404
|View full text |Cite
|
Sign up to set email alerts
|

Selectin polymorphisms and perinatal morbidity in low‐birthweight infants

Abstract: Our results underline the importance of L-selectin in perinatal pathology, but further studies are needed to evaluate the alteration of L-selectin levels in carriers of the 213Ser allele and their possible contribution to premature birth and bronchopulmonary dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…They were selected partly from a cohort of neonates treated at the Second Department of Gynecology and Obstetrics, Semmelweis University (n = 92) and the participants were partly the same as those reported in earlier studies [26][27][28]. The other parts of the neonates (n = 33) were born in Veszprem County Hospital.…”
Section: Patientsmentioning
confidence: 99%
“…They were selected partly from a cohort of neonates treated at the Second Department of Gynecology and Obstetrics, Semmelweis University (n = 92) and the participants were partly the same as those reported in earlier studies [26][27][28]. The other parts of the neonates (n = 33) were born in Veszprem County Hospital.…”
Section: Patientsmentioning
confidence: 99%
“…In a retrospective Hungary-based study Derzbach et al 42 identified 125 LBW infants who were born between 1995 – 1999 and had a GA ranging from 24 – 36 weeks and BW 510-1500 grams. They were compared to 156 full term control infants.…”
Section: Candidate Genes Tag Snps Haplotypesmentioning
confidence: 99%
“…Aydemir et al 21 Härtel et al 9 Abu-Maziad et al 22 Auriti et al 23 Koroglu et al 24 Spiegler et al 25 Abdel-Hady et al 26 Bertalan et al 27 Reiman et al 28 Dzwonek et al 29 van Der Zwet et al 30 Schueller et al 31 Derzbach et al 32 Härtel et al 33 Baier et al 34 Göpel et al…”
Section: Questions (Q)unclassified